Huge hard palate and nasal septum perforation as a presentation of syphilis: A case report - Shahrjerdi, B; Mohamad, I (Bangladesh Journal of Medical Science, 2012)
A patient presented with septal and palatal perforations imposes a diagnostic challenge because various potential causes need to be established. Therefore, elucidating the cause of the septal perforation requires obtaining a thorough history. In addition, it is very important to perform necessary investigations for the patients to determine and fix the underlying disease which cause these complaints. We report a case of patient presented with palatal and septal perforations which later was confirmed to have syphilis. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11737 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12